2012
DOI: 10.1504/ijplm.2012.046442
|View full text |Cite
|
Sign up to set email alerts
|

PLM implementation guidelines – relevance and application in practice: a discussion of findings from a retrospective case study

Abstract: In this paper, a recently conducted product lifecycle management (PLM) implementation project is analysed. The aims are to investigate whether published product lifecycle management (PLM) implementation guidelines are relevant to and used in practice, and, if so, to assess how useful they are for guiding project execution. This paper presents an examination of how a real PLM implementation project was conducted, mapping out the rationale for different courses of action and the effects they had. This paper eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…The guidelines summarised by [14] worked to some extent, although an insufficient coverage was identified. More guidelines (e.g., in literature, at seminars or through communication with PLM experts) should be searched for in order to improve the assessment base.…”
Section: Methods Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…The guidelines summarised by [14] worked to some extent, although an insufficient coverage was identified. More guidelines (e.g., in literature, at seminars or through communication with PLM experts) should be searched for in order to improve the assessment base.…”
Section: Methods Evaluationmentioning
confidence: 99%
“…In this paper, LM solutions has not attracted much attention from the ver, analysis could be based on guidelines for PLM so an be defined as a directional recommendation for wha specific context. Bokinge and Malmqvist [14] summari uidelines (among other PLM implementation guidelin e Table 1) and evaluated the guidelines' relevance and dustry. They found that most of the guidelines were hig uggested that PLM projects should review their plans w d and including a plan for how to apply the guidelines.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations